2003
DOI: 10.1001/jama.289.19.2517
|View full text |Cite
|
Sign up to set email alerts
|

Race, Quality of Care, and Outcomes of Elderly Patients Hospitalized With Heart Failure

Abstract: EART FAILURE IS A NATIONAL epidemic, affecting nearly 5 million persons in the United States, with an additional 550 000 diagnosed each year. 1 This burden is disproportionately borne by black Americans, who have a higher incidence and prevalence of heart failure than members of other racial groups. 1 Despite this greater burden, black patients may receive less intensive and poorer-quality care for heart failure than whites. 2-5 Some studies, however, suggest that black patients receive similar quality of care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
149
3
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(172 citation statements)
references
References 52 publications
(49 reference statements)
16
149
3
4
Order By: Relevance
“…Consistent with previous research, black women in our study received a diagnosis of HF at younger ages and were more likely to have comorbidities, limitations in activities of daily living, and a lack of health insurance compared with white women 1, 7, 9, 17, 18, 49. However, racial differences in hospitalization largely remained despite adjustments for these and other risk factors.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Consistent with previous research, black women in our study received a diagnosis of HF at younger ages and were more likely to have comorbidities, limitations in activities of daily living, and a lack of health insurance compared with white women 1, 7, 9, 17, 18, 49. However, racial differences in hospitalization largely remained despite adjustments for these and other risk factors.…”
Section: Discussionsupporting
confidence: 86%
“…Instead, we found that black‐white differences in the number of hospitalizations were most pronounced in the Northeast and West. It is not clear whether or to what extent these differences may be related to possible regional variations in the quality of HF care 17, 55. We encourage additional studies to further validate these findings of patient‐level changes in hospitalizations following an HF diagnosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The availability of genetic ancestry can help differentiate true inherited differences versus the wide range of environmental factors that are associated with self‐identified race, such as socioeconomic status, diet, and healthcare quality and accessibility, all of which can make attempts to understand the underlying cause of race disparities in health outcomes very difficult 37. It is important to interrogate the role of genetic ancestry because socioeconomic factors do not fully explain the critical race disparities in HF outcomes,38 and to try to quantify potential genetic and biological effects. For example, African genetic ancestry is associated with poorer diastolic function parameters in HF patients 39.…”
Section: Discussionmentioning
confidence: 99%